The Maturational Refolding of the β-Hairpin Motif of Equine Infectious Anemia Virus Capsid Protein Extends Its Helix α1 at Capsid Assembly Locus - Chen, Kang (American Society for Biochemistry and Molecular Biology, 2013)
A retroviral capsid (CA) protein consists of two helical domains, CA(N) and CA(C), which drive hexamer and dimer formations, respectively, to form a capsid lattice. The N-terminal 13 residues of CA refold to a β-hairpin motif upon processing from its precursor polyprotein Gag. The β-hairpin is essential for correct CA assembly but unexpectedly it is not within any CA oligomeric interfaces. To understand the β-hairpin function we studied the full-length CA protein from equine infectious anemia virus (EIAV), a lentivirus sharing the same cone-shaped capsid core as HIV-1. Solution NMR spectroscopy is perfectly suited to study EIAV-CA that dimerizes weaker than HIV-1-CA. Comparison between the wild-type (wt) EIAV-CA and a variant lacking the β-hairpin structure demonstrated that folding of the β-hairpin specifically extended the N terminus of helix α1 from Tyr(20) to Pro(17). This coil to helix transition involves the conserved sequence of Thr(16)-Pro(17)-Arg(18) (Ser(16)-Pro(17)-Arg(18) in HIV-1-CA). The extended region of helix α1 constituted an expanded EIAV-CA(N) oligomeric interface and overlapped with the HIV-1-CA hexamer-core residue Arg(18), helical in structure and pivotal in assembly. Therefore we propose the function of the maturational refolding of the β-hairpin in CA assembly is to extend helix α1 at the N terminus to enhance the CA(N) oligomerization along the capsid assembly core interface. In addition, NMR resonance line broadening indicated the presence of micro-millisecond exchange kinetics due to the EIAV-CA(N) domain oligomerization, independent to the faster EIAV-CA(C) domain dimerization.